Annealing time effect on the optical properties of Zn(O,OH,S) films onto ZnO seed layer under un-vacuum ambient - Fatma Özütok; Emin Yakar (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In this study, Zn (O,OH,S) films were synthesized onto ZnO seed layers by chemical bath deposition, which were annealed at 500 °C. The differences of structural, morphological and detailed optical properties of the films were investigated depending on the annealing time (between 30 min. and 90 min.). While samples of 30.min and 90 min. showed decomposed structures, sample of 60 min. showed different dimensions of nano-flower structures. Although all films had ZnO-hexzagonal crystal structure, the most obvious ZnS-related peaks were observed in the sample of 90 min. Optical absorption edge was shifted at 362 nm from Uv-Vis spectroscopy. Although ZnO, Zn(OH)2 vibration related peaks were so sharp, ZnS vibration peaks were so weak for all samples from FTIR. The PL intensities were differential depending on the annealing time but defect state-corresponding peaks were similar for each films.